Agrobacterium-mediated transformation of pMDC140 plasmid containing the wheatwin2 gene into the Tadong rice genome - Tzyy, Eric Jiann Chong; Jun, Jovita Wong; Zaleha Abdul Aziz; Chia, Lock Tan; Sreeramanan Subramaniam; Mariam Abd. Latip; Lee, Ping-Chin (MDPI AG, 2021)
Blast disease resulting from Magnaporthe oryzae fungal infection reduces annual rice yield by up to 30% globally. The wheatwin2 (wwin2) is a pathogenesis-related (PR) gene that encodes for a PR-4 protein with chitinase properties that is capable of degrading chitin, a major constituent of certain fungal cell walls. However, the potential for wwin2 to contribute to M. oryzae resistance in rice is unclear. This study reports the construction of a pMDC140 vector carrying the wwin2 gene and its Agrobacterium-mediated transformation into the Tadong rice genome. In brief, the wwin2 gene was synthesized and integrated into a pMDC140 vector using Gateway cloning technology and was transformed into the Tadong rice genome. Our results show a promising high transformation rate, with more than 90% of the transformed rice calli expressing β-glucuronidase (GUS), the reporter gene marker. The expression of the wwin2 gene in transformed rice calli was further confirmed using quantitative real-time polymerase chain reaction. In conclusion, a pMDC140-wwin2 vector was constructed, which had a high transformation rate and could consistently induce expression of the GUS and wwin2 genes in Tadong rice. Data of this study is beneficial for subsequent in vitro and M. oryzae-infected field experiments to confirm the defense mechanism of the wwin2 gene towards blast disease in rice.